Patterns and inequities in pyogenic arthritis-related mortality in the United States from 1999–2020 - Usama Qamar; Maaz Asif; Farhan Naeem; Eisha Mazhar (Exploration of Musculoskeletal Diseases)
Pyogenic arthritis (PA) related mortality trends have not been studied well across various demographics in the United States (US). This cross-sectional study aimed to evaluate these trends among the US population aged ≥ 25 years from 1999–2020 using data from the CDC WONDER database. We identified all the deaths where PA was listed as the underlying or contributing cause of death, using the ICD-10 code M00. Age-adjusted mortality rates (AAMRs) were calculated per 1 million US population and the Joinpoint regression model was used to assess the annual mortality trends by calculating the annual percent change (APC) in AAMRs. Between 1999 and 2020, 13,965 total deaths occurred among US adults aged ≥ 25 years with an AAMR of 2.94. The overall AAMR of PA increased significantly from 1999 to 2020 with an APC of 2.01 (p < 0.01). Males and older adults had consistently higher AAMRs than their respective counterparts. Non-Hispanic (NH) American Indians/Alaska Natives and NH Blacks/African Americans had higher mortality rates compared with other racial groups. The Midwest had the highest overall AAMR, followed by the West, Northeast, and South regions. In conclusion, PA mortality has been on the rise and targeted interventions are warranted to reduce disproportionate mortality rates among vulnerable populations.